2011
DOI: 10.1088/0964-1726/20/6/067001
|View full text |Cite
|
Sign up to set email alerts
|

The patch effect on the vibro-acoustic coupling of an irregular enclosure backed with a PZT-bonded panel

Abstract: This paper deals with the vibro-acoustic coupling of an irregular enclosure covered with a PZT-bonded panel. The modeling of the system is developed with full consideration of the acoustic-structural-piezoelectric interactions between the actuated panel and the enclosure, along with the modeling of the irregular shape of the enclosure. Simulations are conducted to investigate the effect of the actuation patch on structural modal modification, and subsequently on the structural-acoustic coupling mechanism. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Finally, based on the displacement continuity between the mass and the membrane on every collocation point, we have . (10) Substituting Eqs. ( 5) -( 9) into Eq.…”
Section: A Eigenvalue Problem Of the Mammentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, based on the displacement continuity between the mass and the membrane on every collocation point, we have . (10) Substituting Eqs. ( 5) -( 9) into Eq.…”
Section: A Eigenvalue Problem Of the Mammentioning
confidence: 99%
“…[7][8] It was realized that the added small mass loadings can significantly affect vibration behaviors and acoustic transmission properties of the membrane, 9 which provided many interesting potential applications in sound or noise control schemes. 10 However, compared with vibroacoustic studies of the pure membranes, studies on membranes with distributed masses are not well established because of the difficulty from its complex multiconnected boundary conditions. The prototype proposed by Yang et al now is recast into more general concept of membranetype metametrials, 1,2 which have been suggested to possess excellent acoustic properties for lowfrequencies sound insulation.…”
Section: Introductionmentioning
confidence: 99%
“…Static and dynamic behaviors of the beams with segmented piezoelectric actuators are modeled theoretically, and verified by tests (Crawley and De Luis, 1987), and extended to isotropic and anisotropic plates (Crawley and Lazarus, 1991). Dynamic and static analyses of isotropic and laminated composite plates with piezoelectric actuators/sensors are presented (Koshigoe and Murdock, 1993;Kozupa and Wiciak, 2010;Li, 2011;Liew et al, 2004;Reddy, 1999;Yang and Zhang, 2006). Active random vibration controls of the isotropic and laminated composite plates/shells using piezoelectric actuators/sensors are studied (Dogan and Vaicaitis, 1999;Poulin and Vaicaitis, 2004;Wang and Vaicaitis, 1998;Wei and Vaicaitis, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In theory, the acoustic behavior in an enclosed space has been well studied. Different boundary conditions, such as rectangular and cylindrical cavity shape or irregular enclosures all show significant effects on the distribution of the internal acoustic pressure [ 10 13 ]. Thus, the vibratory structure in an enclosed space is susceptible to variation of the boundary conditions.…”
Section: Introductionmentioning
confidence: 99%